Comprehensive analysis of circRNAs and lncRNAs involvement in the development of skeletal muscle in myostatin-deficient rabbits - Ling Li; Ting Zhang; Muhammad Farhab; Xiao-Xiao Xia; Abu Musa Md Talimur Reza; Paing Oo Kyaw; Fenglei Chen; Esraa Aly Sayed Ismail; Gang Xue; Ping Zhong; Yong Cheng; Yu-Guo Yuan (Animal Biotechnology)
Myostatin (MSTN) protein, lncRNAs, and circRNAs regulate skeletal muscle growth and development. This work aims to compare the expression patterns of circRNAs and lncRNAs in the gluteus maximus tissue of wild-type (WT) and MSTN gene knockout (KO) rabbits. Within the gluteus maximus tissue of three WT and four MSTN KO rabbits, we analyzed the expression profiles of circRNAs and lncRNAs. After identifying the differently expressed RNAs, the biological pathways implicated were ascertained by performing enrichment analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO). We identified differences in the expression of 251 circRNAs (79 upregulated and 172 downregulated), 176 lncRNAs (53 upregulated and 123 downregulated), and 1178 mRNAs (408 upregulated and 770 downregulated) between WT and MSTN KO rabbits. Target genes were significantly enriched in pathways associated with protein synthesis and catabolism, such as oxidative phosphorylation, ubiquitin-mediated proteolysis, the FoxO signaling pathway, and the pentose phosphate pathway, as identified through GO and KEGG enrichment analyses. The constructed network indicates that a class of circRNAs and lncRNAs is engaged in MSTN-mediated regulation of skeletal muscle development. These findings provide valuable insights for innovative therapeutic, diagnostic, and preventive approaches to muscle disorders.